Two new species of Marantaceae from Reserva Natural Vale, Espírito Santo state, Brazil - Fraga, Fernanda Ribeiro De Mello; Braga, João Marcelo Alvarenga (Phytotaxa, 2025)
We describe two new species of Marantaceae of the Brazilian Atlantic Forest. These species were discovered in northern Espírito Santo state, inside Reserva Natural Vale. Ctenanthe brevibractea is here compared to C. lanceolata, and can be distinguished by its overall shorter stature, glabrous leaf sheath, inflorescence rachis with shorter internodes, component bracts obovate-acuminate, deciduous, holding 1–2 cymules, per cymule with one bracteole, and flowers with solitary, spathulate outer staminodes. Saranthe rufopilosa is most similar to S. leptostachya, but differs by having 2-nodated inflorescences, and indumentum of long stiff reddish trichomes disposed on peduncles, rachis, internodes of inflorescences, cymule peduncles, pedicels, sepals and ovary. Their distribution maps and photographs are also provided.